2005
DOI: 10.1128/aac.49.7.2921-2927.2005
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptide Therapeutics for Cystic Fibrosis

Abstract: Greater than 90% of lung infections in cystic fibrosis (CF) patients are caused by Pseudomonas aeruginosa, and the majority of these patients subsequently die from lung damage. Current therapies are either targeted at reducing obstruction, reducing inflammation, or reducing infection. To identify potential therapeutic agents for the CF lung, 150 antimicrobial peptides consisting of three distinct structural classes were screened against mucoid and multidrug-resistant clinical isolates of P. aeruginosa, Stenotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(140 citation statements)
references
References 38 publications
3
136
0
1
Order By: Relevance
“…They are part of the innate immune response (Ganz, 2003;Zanetti, 2004) and have been shown to kill bacteria through the disruption of the inner membrane (Brogden, 2005) and also through inhibition of intracellular processes (Patrzykat et al, 2002). APs have been proposed as agents for treatment of infections by other CF lung pathogens, such as Pseudomonas aeruginosa (Zhang et al, 2005). Unfortunately, due to the extraordinary resistance of B. cenocepacia to the killing effects of APs, they are unlikely to be useful agents for treatment of lung infections by B. cenocepacia.…”
Section: Introductionmentioning
confidence: 99%
“…They are part of the innate immune response (Ganz, 2003;Zanetti, 2004) and have been shown to kill bacteria through the disruption of the inner membrane (Brogden, 2005) and also through inhibition of intracellular processes (Patrzykat et al, 2002). APs have been proposed as agents for treatment of infections by other CF lung pathogens, such as Pseudomonas aeruginosa (Zhang et al, 2005). Unfortunately, due to the extraordinary resistance of B. cenocepacia to the killing effects of APs, they are unlikely to be useful agents for treatment of lung infections by B. cenocepacia.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] Conversely, there are reports that passage under sub-MIC concentrations produced lesser increases in experimental MIC for antimicrobial peptides than conventional antimicrobial agents, and no cross-resistance has been observed among different antimicrobial peptides. 25,26 Thus, it is expected that bacteria will find it difficult to acquire resistance to antimicrobial peptides. 22,27 Antimicrobial peptides interact with bacteria by electrostatic forces between their positive amino acid residues and negative charges present on the bacterial cell surface, thereby causing damage to the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial peptides have been successfully applied in cystic fibrosis. They were applied via aerosolization [92]. Vector-based mediated delivery of gene encoding for antimicrobial peptides were used in cancer therapy [93].…”
Section: Discussionmentioning
confidence: 99%
“…As several studies have shown that no bacterial or viral resistance against AMPs has developed so far [42][43][44], antimicrobial peptides could be a powerful tool in the therapy of acute or chronic infectious diseases in the future. As there is a growing number of treatment-resistant bacteria and viruses causing immense problems and exploding costs in public healthcare (Figure 3), it is a promising therapeutic concept to develop treatments involving the application of these molecules, sole or in combination with conventional antibiotics.…”
Section: Antimicrobial Activitymentioning
confidence: 99%